(untitled) (Scientific Journal of Actuarial Finance and Accounting, 2025)
The structural transformation of Uzbekistan’s banking sector highlights the need to evaluate the outcomes of corporate governance reforms. This study explores how recent reforms impact the profitability of state-owned banks in Uzbekistan. Utilizing panel data analysis with a Fixed Effects model and Bootstrapping techniques, the research investigates the relationship between governance variables—such as board composition, board size, gender diversity, audit and risk committee size, and government ownership—and profitability indicators, including Return on Assets (ROA) and Return on Equity (ROE). The results indicate that while government ownership enhances financial stability, larger audit committees may reduce efficiency. These findings offer valuable insights for policymakers in emerging markets, emphasizing the importance of aligning governance practices with local economic and institutional conditions